Adsorption of platinum-group metals and molybdenum onto aluminum ferrocyanide in spent fuel solution. (December 2017) - Onishi, Takashi; Sekioka, Ken; Suto, Mitsuo; Tanaka, Kosuke; Koyama, Shin-ichi; Inaba, Yusuke; Takahashi, Hideharu; Harigai, Miki; Takeshita, Kenji
Abstract: Separation of platinum-group metals (PGMs: Ru, Rh, Pd) and Mo from high-level liquid waste (HLLW) makes the vitrification process more stable. Aluminum ferrocyanide (AlHCF) has been synthesized, and it is suitable for the simultaneous recovery of PGMs and Mo from HLLW. In this study, an adsorption experiment onto AlHCF was conducted in a spent fuel solution prepared from an irradiated MOX fuel. An adsorption experiment in a simulated HLLW with 26 elements was also conducted as reference. As a result, both Pd and Mo have been successfully adsorbed on AlHCF in both the spent fuel solution and the simulated HLLW. Americium was not adsorbed onto AlHCF as tri-valent lanthanide ions were.